Consumer identity and marketing implications: Indian urban youth. (16th February 2016) - Kartik, Deval; Willis, Rob; Jones, Cassie
Abstract: Youth consumption has been an area of research interest as well as societal concern. Globalization and proliferation of media have been cited as the main reasons for rise in consumption, especially among youth. This paper has examined how the Indian Urban youth represent their Consumer Identities through their narratives. In 1991, India opened up to Globalization and its effect on the youth consumption is now wide spread. Studies in other parts of the world have shown youth to be 'Raving Hedonists' and 'Squanderer' as well as Rational and Economical Consumers. An empirical approach was taken to establish the typology of Indian Youth Consumers. Empirical data for this research was collected by conducting in‐depth interviews in 2013, covering various states of India, with students in the age group of eighteen to twenty three years, who are financially dependent on their parents. Forty in‐depth interviews, representing thirteen distinct linguistic identities were conducted and analysed. Studies done in other parts of the world such as UK, Finland, Norway and Belgium have established typologies of youth consumers such as Hedonist, Squanderer, Rational and Economical Consumer Identities. While these Consumer Identities exist among Indian Urban Youth, the researchers have identified additional Consumer Identity Typologies of Reluctant, Dependent and Aspirant Consumers. The youth in India is somewhat similar to youth elsewhere and yet has its own distinction as consumers. The fact that India has a very high youth population makes this study significant.